Phytochemical Composition Antioxidant and Anti-Inflammatory Activity of Artemisia dracunculus and Artemisia abrotanum - Mădălina Țicolea; Raluca Maria Pop; Marcel Pârvu; Lia-Oxana Usatiuc; Ana Uifălean; Floricuța Ranga; Alina Elena Pârvu (MDPI AG, 2024)
This study aimed to investigate the antioxidant and anti-inflammatory activities mechanism of Artemisia dracunculus (A. dracunculus) and Artemisia abrotanum (A. abrotanum) ethanol extracts in acute rat inflammation induced in Wistar male rats with turpentine oil. The characterization of the polyphenolic compounds in the extracts was conducted using UV-Vis and Fourier-transform infrared spectroscopy and high-performance liquid chromatography coupled with mass spectrometry techniques. The antioxidant activity of the extracts was evaluated in vitro by DPPH, FRAP, H2O2, and NO scavenging tests and in vivo by measuring the total oxidative status (TOS), total antioxidant capacity (TAC), oxidative stress index (OSI), 8-hydroxy-deoxyguanosine (8-Oxo-dG), advanced oxidation protein products (AOPP), malondialdehyde (MDA), nitric oxide (NO), 3-nitrotyrosine (3NT), and total thiols (SH). Inflammation was evaluated by measuring nuclear factor-kB-p65 (NfkB-p65) and NLRP3 inflammasome activation with IL-1β, IL-18, and gasdermin D. Liver and renal toxicity was determined following transaminases (ALT and AST), creatinine, and urea. The experimental results indicated that A. dracunculus and A. abrotanum ethanol extracts have moderate in vitro antioxidant activity and had in vivo antioxidant activity and an anti-inflammatory effect by NfkB-p65, IL-1b, IL-18, and gasdermin D serum level reduction. The antioxidant activity correlated with the chemical composition of the extracts. These results bring evidence-based use of A. dracunculus and A. abrotanum's in traditional and contemporary medicine.